Analisis Kebijakan Penyertaan Modal pada Perusahaan Daerah (PD) Sindangkasih Multi Usaha - Wildan Ahmil; Ai Siti Farida; Khaerul Umam (Administratio, 2022)
This study aims to find out how to fulfill the objectives of the capital investment policy that has been carried out by the Regional Government of Majalengka Regency to one of their regional-owned enterprises, namely PD Sindangkasih Multi Usaha. Research method used in this study is mixed methods with concurrent transformative strategies. Qualitative data obtained through unstructured interviews and observations, while for quantitative data obtained through the study of documents related to the indicators that will be examined. The results of the study show that the objectives of equity participation as stated in the regulation of equity participation have been achieved, but further steps are needed to determine whether there is a need for a policy of capital investment again or not.